Midwinter Arctic leads form and dissipate low clouds - Xia Li (Nature Portfolio, 2020)
Cracks in Arctic sea ice (leads) are becoming more prevalent and widespread, yet studies regarding their impacts on clouds are limited. Here, contrary to the present understanding, diverse observations and modelling simulations show that higher leads concentrations do not necessarily result in more low clouds.